Neuro-occlusal stimulation, a crucial effect on the asymmetric development of the paediatric stomatognathic system.: A 3D morphological and insilico study. - Ortún-Terrazas, Javier; Fagan, Michael J.; Cegoñino, Jose; Pérez del Palomar, Amaya (Jornada de Jóvenes Investigadores del I3A, 2019)
A statistical study of the relationship between the neuro-occlusal stimulus produced in paediatric patients with unilateral bitting and the abnormal stomatognathic system growth is proposed to improve early treatments and avoid surgical treatments later in life. Therefore, 3D morphological and finite element analyses were performed to study malformations and function imbalances, respectively.